ANALYSIS OF REGIONAL ORIGINAL REVENUE, CAPITAL EXPENDITURE, AND INTERGOVERNMENTAL REVENUE ON LOCAL GOVERNMENT FINANCIAL PERFORMANCE - HARI SRIWIJAYANTI; NIKE APRIYANTI (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2020)
This research analyzes the influence of local revenue (PAD), capital expenditure, and intergovernmental revenue on financial performance. The sample used in this research is the financial report of the District and City Governments in West Sumatra Province. The analysis used in this research is a classical assumption test, model selection, and panel data regression using Eviews 9 software. The results show that 1. The PAD variable partially has a positive and significant effect on financial performance. 2. The capital expenditure variable partially has a positive and significant effect on financial performance. 3. The intergovernmental revenue variable partially has a negative and significant effect on financial performance. 4. The PAD, capital expenditure, and intergovernmental revenue variables positively and significantly affect financial performance.